Pengembangan Media Puzzle IPA Materi Metamorfosis Makhluk Hidup Kelas IV UPT SDN 023 Pandau Jaya : Penelitian - Erleni Mustika Sari; Dea Mustika (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to develop learning media in the form of puzzles on the subject of metamorphosis of living things for fourth grade students at UPT SDN 023 Pandau Jaya. The research method used is research and development (R&D) with the ADDIE model, but this study was only conducted up to the development stage. Research data was obtained through validation by subject matter experts, language experts, and media experts, as well as responses from teachers and students. Research instruments in the form of expert validation sheets and response questionnaires were used to assess the feasibility and practicality of the product. Qualitative data were obtained from comments and suggestions for improvement, while quantitative data in the form of assessment scores were analyzed using descriptive percentage techniques. The validation results showed that the puzzle media obtained an average of 95.6% in the “highly valid” category. Subject matter expert validation was 95.8%, language expert validation was 95%, and media expert validation was 96.25%, all of which fall into the “highly feasible” category. Practicality testing through teacher responses yielded a percentage of 97.5% and student responses 100%, both falling under the “highly feasible” category. Thus, the puzzle-based media on the topic of metamorphosis of living organisms is suitable for use as an innovative learning medium alternative to enhance motivation and understanding among elementary school students.